OVERVIEW OF THE BIOENERGY POTENTIAL OF ENERGY CROPS FOR THE PRODUCTION OF DIFFERENT TYPES OF BIOFUELS - TOKARCHUK, Dina (Herald of Khmelnytskyi National University. Economic sciences, 2024)
Energy security is one of the key challenges of today, which requires the search for renewable energy sources to replace fossil fuels. In this context, energy crops used for the production of biofuels are becoming increasingly important. A separate classification of energy crops according to various characteristics is proposed, which allows taking into account their economic, technological and ecological potential; examples of cultures are given. The bioenergy potential of energy crops for the production of biofuels of the first, second and third generations was studied and the raw material base for their production was systematized. Particular attention is paid to the global use of energy crops such as wheat, corn, sugar cane, rapeseed, as well as vegetable oils, which provide the basis for the production of biofuels. It has been found that the production of first-generation biofuels, such as bioethanol from sugar and starch-containing crops and biodiesel from vegetable oils, is predominant in the world. However, given the fact that traditional crops are used for the production of first-generation biofuels, there may be a threat to food security, which is an incentive for the production of second- and third-generation biofuels. The expediency of attracting low-productivity lands of Ukraine for the cultivation of perennial bioenergy crops, which will provide a stable raw material base for the production of biofuels, is substantiated. It is substantiated that the use of traditional and special energy crops contributes to reducing dependence on fossil resources and reducing greenhouse gas emissions. The results of the study confirm that the development of bioenergy is a strategically important area of Ukraine's energy and environmental policy, and the effective use of energy crops contributes to the global transition to renewable energy sources.
Keywords: biofuel energy crops; bioenergy potential; bioethanol; biodiesel; biogas; solid biofuels